2019
DOI: 10.1111/wvn.12405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotics, Prebiotics, and Synbiotics on Calcium Homeostasis and Bone Health With Aging: A Systematic Review

Abstract: Background: Calcium homeostasis and bone health are an increasing concern for middleaged and older adults. Many studies have explored the positive effects of probiotics, prebiotics, or synbiotics on serum calcium and bone mineral density (BMD) or other parameters related to bone health. However, the participants, the species, doses and duration of interventions, outcomes, and measurements varied among these studies.Aims: To systematically evaluate the effect of probiotics, prebiotics, or synbiotics on maintain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…In contrast, in a meta-analysis combining 5 trials using prebiotics, 2 trials using probiotics, and one trial using a synbiotic (prebiotic and probiotic combined), no significant benefit to bone was found. 217…”
Section: Dietary Bioactivesmentioning
confidence: 99%
“…In contrast, in a meta-analysis combining 5 trials using prebiotics, 2 trials using probiotics, and one trial using a synbiotic (prebiotic and probiotic combined), no significant benefit to bone was found. 217…”
Section: Dietary Bioactivesmentioning
confidence: 99%
“…Nevertheless, human studies have yielded divergent results (Table 1). For example, a meta-analysis compiling data from RCTs involving 564 subjects states that even though the consumption of probiotics increases serum calcium levels, it does not improve markers of bone health [187]. In contrast, Jansson et al [188] conducted a randomised, double-blind, multicentre placebo study in Sweden involving 249 postmenopausal women for 12 months, where they found three Lactobacillus species prevented bone loss in the lumbar spine.…”
Section: Therapeutic Approach Against Ageing: Influencing the Gut Mic...mentioning
confidence: 99%
“…In humans, earlier research concluded that symbiotic bacteria restore the skin barrier; protect against photoaging; and improve hair quality [ 290 ], cognitive function, and aging-mediated memory impairment during aging [ 291 - 293 ]. Liu et al also argued that ingesting symbiotics significantly upregulated serum calcium concentrations in older individuals, although its benefits to bone health remained ambiguous [ 294 ].…”
Section: Emerging Approaches: Interventions In the Gut Microbiota In ...mentioning
confidence: 99%